ผลของการใช้โปรแกรมพัฒนาพฤติกรรมบริการพยาบาลของพยาบาลวิชาชีพ ที่สร้างความประทับใจต่อความพึงพอใจของ ผู้ป่วยห้องอุบัติเหตุและฉุกเฉิน - สมศิริ สายภัทรานุสรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To compare the patient satisfaction before and after using impressive nursing service behavior development program in the first and the third week. Research subjects were 60 patients who receiving care form the 20 professional nurses at the accidental and emergency unit, Bhumibol Adulyadej Hospital. The patients were equally divided into one experimental and one control group using matched paired technique. Research instruments which were developed by the researcher and tested for content validity by a panel of experts were an impressive nursing service behavior development program, a nursing service impressive behavior checklist, and a patient satisfaction questionnaire. The reliability of the above mentioned checklist was .94 and the Cronbach alpha coefficient of the questionnaire was .91. Statistical techniques used in data analysis were mean, standard deviation and t-test. Major research findings were as follows: 1. The satisfaction of patients receiving nursing care in the accidental and emergency unit in the first week after using the impressive nursing service behavior development program was significantly higher than before using the above mentioned program, at the .05 level. 2. The satisfaction of patients receiving nursing care in the accidental and emergency unit in the third week after using the impressive nursing service behavior development program was significantly higher than before using the above mentioned program, at the .05 level.